Kualifikasi Seorang Diaken dalam Gereja Berdasarkan 1Timotius 3:8-13Kajian Eksegesis Metode 4 Lapisan Makna Alkitab - Mainyer for Jaya Gulo; Yaaro Harefa (LPPM STT Baptis Kalvari, 2024)
This article is the result of research conducted using qualitative methods. The author uses this method by collecting various library data sourced from books, theses, and other articles. In addition, in this research, the author also approaches the exegesis method by using the 4 layersof biblical meaning, namely, layer 1: Historia/Sarkic, layer 2: Noetic/spiritual meaning, layer 3: Psychic/moral, and layer 4: Anagogic/Escatological. These 4 layers are very helpful for the author to approach exegesis. In this study, the author provides an understanding of the importance of the character and example of a servant of God who reflects Christ. Based on the findings that a servant of God who becomes a deacon must have integrity, be able to control himself, have faith and live the teachings of Christ, have a good household example and be able to be responsible for his family, making the position of deacon a bridge in preaching Christ. These deacon qualifications are very important for all ministers of God because ministers of God are people serving God and of course the guideline for serving is Christ Himself. In this study, the author examines the requirements or qualifications to become a deacon based on the context of 1Timothy 3:8-13